'Really really different different': rurality, regional schools and refugees. Issue 2 (4th March 2017) - Colvin, Neroli
Abstract: This article explores the dynamics of difference-making in a regional Australian town. Despite Australia's high levels of cultural diversity, many rural and regional areas remain predominantly 'white' spaces, presided over by people of Anglo-Celtic ancestry but with small populations of indigenous Australians. Over the past decade, however, a growing number of regional centres have become home to refugees from a range of African, Middle Eastern and South-East Asian countries. This study draws on interview, observational and documentary data to shed light on the experiences of people in one such town, focusing on schools as sites of everyday social contact and significant mediators of identity formation and settlement outcomes. A key aim of the article is to illuminate the ways in which constructions of rurality and of difference intersect with local histories and resources to shape relations between the original, 'old' and newest settlers.